Die naturräumliche Gliederung Nord-Äthiopiens - Troll, Carl (ERDKUNDE, 1970)
The highland of Northern Ethiopia (Eritrea) is a tilt block of the crystalline Nubian-Arabian Shield rising from the lowland of the Sudan up to a maximum of 3,250 metres at the edge of the Red Sea trench. From Asmara south wards it is overlain by various layers of sedimentary and volcanic formations, by the mesozoic Adigratian Sandstone, jurassic Antalo Limestone, Upper Sandstone and a basalt trap cover of, at most, 3,000 metres thickness. The base of the trap cover is a prebasaltic peneplain. This peneplain is marked by a ferric crust formation which covers not only the crystalline schists in the north but also the Adigration Sandstone in the south. The origin of this ferric crust is still unsure but, because of its resistance to erosion, it forms table mountains and plateaux with particularly well-defined edges ('Plateau rouge'). Since Dainelli, it has been regarded as a fossil lateritic soil formation, although others, for example Schottenloher, have seen it as a much altered early tuff eruption layer. Climatologically, Eritrea offers a special case of tropical mountains. In addition to a division into thermal altitudinal steps, there is a zonation of seasonal precipitation dependent on orography. The Sudanese Lowland, the western slopes and the high tableland ('Altipiano') receive tropical-zenithal summer rain and are dry in winter. The coastal lowland of the Red Sea receives only very weak winter rain. Summer and winter rain regimes overlap on the eastern slopes of the highland in a complicated fashion. The winter rains become stronger on the mountain slopes in the form of orographic rain and, from 1,200 metres upwards, heavy rain mists form on exposed slopes. On the edge of the Altipiano they cease almost suddenly forming a cloud and mist front. The summer rains diminish in regular fashion from this edge to the base of the slopes and are wholly absent in the Red Sea lowland. In the sheltered valleys and basins of the eastern slope winter rains are absent but, in compensation, summer rains prevail as on the Altipiano. The plant cover shows all the possible contrasts from the hot desert to the tropical-montane rain and mist forests. Because of the juxtaposition of summer rain climates with winter rain climates in a situation of very small seasonal temperature variations, vegetation types which are hygrologically and thermally the same are found in a phenologically inverted relationship. This situation exists on the hot steppes as well as on the edge of the Altipiano. A unique vegetation type is the tropical deciduous forest (com bretaceous woodland) found on the eastern slopes between 400 metres and 1,200 metres above sea level with moderate rainfall at all times of year, and thus without the usual contrast between rainy and dry seasons. The increase in precipitation on the highland towards the south and south west is expressed in a descent of the upper limit of aridity in the valleys and on the slopes in this direction. South of the Takaze, a misty zone with very moist upland forest has been formed on the slope of the Semien Highland under the influence of the African south west Monsoon. This has created a vegetation profile the very opposite of that found in Eritrea. The map (Supplement VII) shows the orographic regionalisation, the geological subsoil, the major forms and the distribution of precipitation, divided according to the rainfall totals for the winter and summer halves of the year. Vegetation is shown only in a west-east profile.